2020
DOI: 10.1108/mmms-03-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment and optimization of hybrid composite patch repair of aircraft structure

Abstract: PurposeIn this article, a novel hybrid composite patch consisting of unidirectional carbon fiber and glass fiber is considered for repair of the aircraft structure. The purpose of this paper is to assess the performance of hybrid composite patch repair of cracked structure and propose an optimized solution to a designer for selection of the appropriate level of a parameter to ensure effective repair solution.Design/methodology/approachElastic properties of the hybrid composites are estimated by micromechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This bonding method reduces stress concentration around the crack's leading edge, resulting in an overall improvement in the structural fatigue life. The principal benefit of the composite patch repair technique lies in its ability to evenly distribute stress across the adhesive area, stress concentrations are the avoided, unlike riveting or bolting where stress concentration zones are inevitable (Makwana and Shaikh, 2020; Chamorro-Cruz et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This bonding method reduces stress concentration around the crack's leading edge, resulting in an overall improvement in the structural fatigue life. The principal benefit of the composite patch repair technique lies in its ability to evenly distribute stress across the adhesive area, stress concentrations are the avoided, unlike riveting or bolting where stress concentration zones are inevitable (Makwana and Shaikh, 2020; Chamorro-Cruz et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have adopted a design of experiments (DOE) approach to investigate the effect of material properties and dimensions on repair performance, to reduce computational and experimental time [11]. The hybridization of multiple volume fractions of fibers in composite patches of varying stiffness has been studied to identify optimal parameters for minimizing SIF [12]. The lamina composite patch has significant effect while having the fiber direction perpendicular to the crack length and this has been proved through the finite element (FE) simulations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Aabid et al [11] demonstrated the utilization of composite patches with varied parameters in their studies. Makwana and Shaikh [12] examined the hybridization of different fiber volume fractions in composite patches with varying stiffness for minimizing the SIF. The study demonstrated the combination of bonding and drilled holes knowing a hybrid repair approach to repair the aircraft structures (thin-plates) through elastoplastic analysis [13].…”
mentioning
confidence: 99%